GREENSHIP AUDIT SEBAGAI UPAYA MEWUJUDKAN KONSEP PENYELENGGARAAN BANGUNAN GEDUNG HIJAU HOTEL HR YOGJAKARTA - Bambang Triantono (Conference In Business, Accounting, And Management (CBAM), 2015)
Green movement booming today not only aims to protect natural resources, but also implemented as the efficiency of energy use and minimize damage to the surrounding environment. Socialization towards mitigation and adaptation to climate change continues to be an ongoing Indonesian government, but not all elements of the community already know and understand about both. Form of the solution of choice is to apply the concept of Green Architecture, or Green Building which is now run by the government, What exactly is the meaning of audit related to the environment and buildings against the elements inherent in the character of green building itself. The audit role is to evaluate the operation of the building embodies the concept of green building government has been some regulations related to the problem. The focus of the paper is to collaborate with the auditÂ of how the application of the concept of green building standards greenship application. The standard to be achieved in the implementation of GREENSHIP is an attempt to realize a concept of environmentally friendly green building since its launch until the operational planning phase of implementation. Â Keywords: Greenship, Audit, Green Building